Digital Transformation in Non-Communicable Disease Management in Pregnant Women: The Effectiveness of Telemedicine on Patient Therapy Compliance - Santy Irene Putri; Siti Asiyah; Dian Jayantari Putri K. Hedo; Dewi Kurnia Sari (Newinera Publisher, 2026)
Non-Communicable Diseases (NCDs) in pregnant women, such as gestational diabetes and hypertension, increase the risk of maternal and perinatal complications. Low adherence to therapy is the main challenge in managing NCDs. Telemedicine has the potential to improve compliance through service access and remote monitoring. This study aims to analyze the factors that affect therapy adherence in pregnant women with NCDs, especially the frequency of telemedicine use, perception of convenience, and trust in services. This study uses a cross-sectional design with a quantitative approach. A total of 185 pregnant women with NCDs in Malang were selected as respondents through purposive sampling. Data were collected using an online questionnaire and analyzed using logistic regression to determine factors influencing therapy adherence. The results of the multivariate analysis showed that the frequency of telemedicine use, the perception of ease of use, and the level of trust in services were factors that significantly affected therapy adherence in pregnant women with non-communicable diseases. Respondents who used telemedicine ≥2 times per month had a higher chance of therapy adherence (AOR = 3.21; 95% CI: 1.33–7.76; p = 0.009). Perceived ease of use also increases the likelihood of compliance (AOR = 2.97; 95% CI: 1.28–6.90; p = 0.011). In addition, high levels of trust in telemedicine services were associated with increased therapeutic adherence (AOR = 2.56; 95% CI: 1.15–5.71; p = 0.022). Telemedicine plays an important role in improving pregnant women's therapeutic adherence to NCDs through increased access, ease of use, and trust in services.